4B08_WS_01e

# 8 more about polynomials ii 2 3 1 2 2 2 x 7 x 15 x 3x

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: +1 ÷ ×2 2 3 x + x +1 6 − 6x 3x − 27 Solution x 3x 5x + + (5 x − 1)(3 x − 2) (3 x − 2)( x + 3) (1 − 5 x )( x + 3) Solution 7 NSS Mathematics in Action Worksheets 4B 6. 8 More about Polynomials (II) 2 3 1 +2 −2 2 x − 7 x − 15 x − 3x − 10 2 x + 7 x + 6 2 Solution 7. x2 y − 3x x 1 × + ÷ 2 2 2 9x + 3y x 9x − y Solution 8. (a) Prove that a + 2 is a factor of 2a 3 − 9a 2 − 11a + 30 . (b) Factorize 2a 3 − 9a 2 − 11a + 30 completely. (c) Hence, simplify a 2 − 10a + 25 a2 − 4 . ×2 2a 3 − 9a 2 − 11a + 30 a − 7a + 10 Solution (a) (b) (c) 8 NSS Mathematics in Action Worksheets 4B 8 More about Polynomials (II) Solutions 8 More about Polynomials (II) L.C.M. Worksheet 8.1 (Basic) a 3b = a 3 × b 1. a 5b 2 = a 5 × b 2 = a3 × b ∴ H.C.F. = a 3b = a5 × b 2 L.C.M. 2. = a 5b 2 a 3b 2c = a 3 × b 2 × c a 2b 4 c 3 = a 2 × b 4 × c 3 ∴ = a 2 × b2 × c H.C.F. = a 2b 2 c = a 3 × b 4 × c3 L.C.M. 3. = a 3b 4c 3 12 x 4 y 8 = 2 2 × 3 45 x 6 y 3 = ∴ 32 × 5 × x 6 × y 3 H.C.F. = 3 × x4 × y3 = 3x 4 y 3 L.C.M. 4. × x4 × y8 15 x 2 yz 7 = = 2 2 × 32 × 5 × x 6 × y 8 = 180 x 6 y 8 3 × 5 × x2 × y × z 7 24 y 2 z 4 = 23 × 3 × y2 × z4 4 ∴ H.C.F. = 3 × y × z = 3 yz 4 L.C.M. 5. 9ab3c 5 = = 23 × 3 × 5 × x 2 × y 2 × z 7 = 120 x 2 y 2 z 7 32 30b 4c 2 = 2 × 3 × 5 45a 3c 4 = ∴ H.C.F. × a × b3 × c 5 × b4 × c2 32 × 5 × a 3 × c4 = 3× c 2 = 3c 2 9 = 2 × 32 × 5 × a 3 × b 4 × c 5 = 90a 3b 4 c 5 NSS Mathematics in Action Worksheets 4B 6. 8 More about Polynomials (II) 3a 2 (b − 2) = 3 × a 2 × (b − 2) 9(b − 2)3 = 32 ∴ H.C.F. × (b − 2)3 = 3 × (b − 2) = 3(b − 2) 2 2 3 L.C.M. = 3 × a × (b − 2) 2 3 = 9a (b − 2) 7. ( a − b )3 ( a + b 2 ) = ( a − b )3 × ( a + b 2 ) ( a − b) 2 (a + 2b) = ( a − b) 2 ∴ H.C.F. = ( a − b) 2 L.C.M. 8. = ( a − b) 3 ( a + b 2 )(a + 2b) 4 x 2 ( x + y )(2 x − y ) = 2 2 × x 2 × ( x + y ) × ( 2 x − y ) 16( x + y ) 3 ( 2 x − y ) 2 = 2 4 ∴ H.C.F. × ( x + y ) 3 × (2 x − y) 2 = 2 2 × ( x + y ) × (2 x − y ) = 4( x + y )(2 x − y ) L.C.M. 9. × (...
View Full Document

## This document was uploaded on 03/03/2014.

Ask a homework question - tutors are online